The necessity of good relationship in the workplace - Yaro, Nasiru (Journal of Professional Secretaries and Office Administrators, 2014)
The forces that affect the way in which we interact at work are many and varied and include: demographic and technological change, globalization, and the impact of the global recession that may increase or limit the role of different players in the workplace relationship. At an individual level, there are the forces of socio-cultural change and the expectations and behaviour of members of society and the way in which they respond to challenges and opportunities around them. Notwithstanding the uncertainty thrown up by the interaction of these often competing dynamic forces, the workplace provides purpose, status, and friendship, allowing people to develop new skills, both technical and social. The ability of Secretarial professionals to manage workplace relations on a day-to-day basis and to get the best from their colleagues has implications for innovation, productivity, quality and reliability, and ultimately the growth of their organizations at national level and the ability to compete on the global stage. This Paper is aimed at developing in Secretarial Professionals, the ability and skill to overcome difficult personalities; obstructions to success; lack of respect or recognition for their role; overcoming challenges set on them by others, including peers; handling toxic bosses, suppliers or clients and coping with uncooperative colleagues among others.